2022
DOI: 10.1007/s00268-022-06874-6
|View full text |Cite
|
Sign up to set email alerts
|

Three Centuries of Appendicectomy

Abstract: Background Save for the contribution of Charles McBurney, who described his eponymous point and the appendicectomy incision, the history of appendicectomy is largely unknown among the medical profession. This review traces the history from the first anatomical depiction of the appendix to the development of open appendicectomy and the recent minimally invasive and non-operative methods. Methods Historical articles, monographs and books containing anatomica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…[11] Traditionally, the standard treatment for acute appendicitis has been an appendectomy, performed either through open surgery or laparoscopically. [12] However, there is growing interest in nonsurgical management for patients with uncomplicated appendicitis. Several studies have demonstrated the e cacy of antibiotic therapy as a nonsurgical alternative for patients with acute uncomplicated appendicitis, reducing the immediate need for surgery.…”
Section: Discussionmentioning
confidence: 99%
“…[11] Traditionally, the standard treatment for acute appendicitis has been an appendectomy, performed either through open surgery or laparoscopically. [12] However, there is growing interest in nonsurgical management for patients with uncomplicated appendicitis. Several studies have demonstrated the e cacy of antibiotic therapy as a nonsurgical alternative for patients with acute uncomplicated appendicitis, reducing the immediate need for surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the literature describes cases of appendix removal using an endoscopic approach -transvaginal, peroral transgastric, and per rectal. [17] Both classical and laparoscopic surgery carry a very low surgical risk, and morbidity and mortality are mainly related to the advancement of appendicitis. [1] Appendix removal surgery can be performed on pregnant women.…”
Section: Surgerymentioning
confidence: 99%
“…The mesoappendix was then separated from the appendix, and the base was then wrapped with two Roeder loops. After that, the base was split, and the stump was invaginated using a purse-string suture that was applied laparoscopically, followed by a Z-stitch [36].…”
Section: Appendicitismentioning
confidence: 99%